Morphometric Study of Nutrient Foramen of Human Adult Humerus and Its Clinical & Medico-legal Implications - Tripathi, Dr. Alok; Sharma, Dr. Vishal; Rupani, Dr. Raja (South Eastern European Journal of Public Health, 2024)
BACKGROUND: Nutrient arteries, along with other arteries supplying the humerus, are crucial not only for the healing of serious injuries such as humeral shaft fractures but also for microsurgical vascularized bone transplantation. Therefore, understanding the precise location and morphometry of nutrient foramen in bones like the humerus is essential to prevent common complications, such as non-union of fractures. This study aims to examine the location and topography of nutrient foramen in the humerus and to establish their clinical & medico-legal significance. MATERIAL METHODS: The study was conducted on 400 dried adult humerus bones of both sexes from Western Uttar Pradesh, sourced from the Department of Anatomy & Department of Forensic Medicine & Toxicology at Mahatma Vidur Autonomous State Medical College, Bijnor. Measurements and observations were carried out using an osteometric board. RESULT: Nutrient foramen was absent in 30 humerus (7.50%), single in 76.50%, and double in 16% of cases. Most humerus had medium-sized foramina (1-2 mm) on both the left and right sides, accounting for 78.80%. The majority of foramina were found on the anteromedial surface (85.02%), with fewer on the posterior surface. Additionally, most foramina were located in the middle third of the humeral diaphysis. CONCLUSION: Surgeons and orthopedists must possess precise knowledge of the number, size, shape, direction, and location of the nutrient foramen to accurately assess the humerus's vascular supply and avoid injury during surgical procedures. Morphometric data is also essential in identifying unknown remains, evaluating the severity and timing of trauma, and determining potential surgical complications in cases of medical malpractice.